2006
DOI: 10.1002/chem.200600040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Radiation Studies of 8‐Bromo‐2′‐deoxyinosine and 8‐Bromoinosine in Aqueous Solutions

Abstract: The reactions of hydrated electrons (e(aq) (-)) with 8-bromo-2'-deoxyinosine (8) and 8-bromoinosine (12) have been investigated by radiolytic methods coupled with product studies and have been addressed computationally by means of BB1K-HMDFT calculations. Pulse radiolysis revealed that one-electron reductive cleavage of the C--Br bond gives the C8 radical 9 or 13 followed by a fast radical translocation to the sugar moiety. Selective generation of a C5' radical occurs in the 2'-deoxyribo derivative, whereas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 55 publications
5
25
0
Order By: Relevance
“…Recently, Chatgilialoglu and colleagues have carried out a series of further mechanistic studies of cyPudNs formation [15][16][17][18][19][20]. In addition to discovering better synthetic routes for cyPudNs, these studies have yielded a number of important mechanistic insights into the stereochemistry and energetics of cyPudNs formation, including the determination of a rate constant for the cyclization reaction (1.6 × 10 5 /s) [20].…”
Section: Cyclopurine Deoxynucleosides: Chemistry Formation and Strumentioning
confidence: 99%
“…Recently, Chatgilialoglu and colleagues have carried out a series of further mechanistic studies of cyPudNs formation [15][16][17][18][19][20]. In addition to discovering better synthetic routes for cyPudNs, these studies have yielded a number of important mechanistic insights into the stereochemistry and energetics of cyPudNs formation, including the determination of a rate constant for the cyclization reaction (1.6 × 10 5 /s) [20].…”
Section: Cyclopurine Deoxynucleosides: Chemistry Formation and Strumentioning
confidence: 99%
“…Indeed, DFT calculations at the B1B95/6-31þ(λ=0.7)G** level show that the π radical anion of 10 (R = Me) is unstable and tends to lose Br -, as previously found for the corresponding radical anion of 8-bromo-2 0 -deoxyadenosine 1 and 8-bromo-2 0 -deoxyinosine. 2 The rate constant for the reaction of e aq -with 11 was found to be (4.9 ( 0.1) Â 10 9 M -1 s -1 at pH 7.6, which is 3 times slower than its protonated form 10. The optical absorption spectrum obtained after the reaction of e aq -with 11 at pH 7 is shown in Figure 3 (black circles).…”
Section: Section Biophysical Chemistrymentioning
confidence: 97%
“…From theoretical considerations the behavior of 8-bromopurine derivatives with respect to hydrated electrons can be attributed to differences in the energy gap between the π*-and σ*-radical anions. [26,30] …”
Section: Generation Of One-electron Oxidized 2'-deoxyguanosine Tautomersmentioning
confidence: 98%
“…[26] Pulse radiolysis revealed that one-electron reductive cleavage of the C-Br bond gives the C(8) radical followed by a fast translocation of the radical site to the sugar moiety. Selective generation of a C(5') radical occurs in the 2'-deoxyriboderivative which undergoes 5',8-cyclization, with a rate constant of 1.4 × 10 5 s -1 .…”
Section: Purine 5'8-cyclonucleosidesmentioning
confidence: 99%